2021
DOI: 10.1007/s12574-021-00525-w
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular myocardial response to exercise in patients with Fontan circulation

Abstract: Background: Exercise stress echocardiography has been used to assess myocardial reserve in various heart diseases. This study examined the ventricular myocardial response to exercise in Fontan patients using exercise stress echocardiography.Methods: Twenty-five Fontan patients and 19 control subjects underwent semi-supine bicycle exercise stress echocardiography in this prospective, single-center, crosssectional study. Pulsed-wave Doppler tissue imaging peak systolic (s') and diastolic (e') velocities, longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Yamazaki et al demonstrated that Fontan patients performed less well at exercise stress echocardiography when compared to healthy subjects; this was largely due to an impaired contractile reserve, chronotropic incompetence, lower ventricle filling capacity, minimal preload variability, and less afterload reduction [ 22 ].…”
Section: Echocardiography In Fontan Circulationmentioning
confidence: 99%
“…Yamazaki et al demonstrated that Fontan patients performed less well at exercise stress echocardiography when compared to healthy subjects; this was largely due to an impaired contractile reserve, chronotropic incompetence, lower ventricle filling capacity, minimal preload variability, and less afterload reduction [ 22 ].…”
Section: Echocardiography In Fontan Circulationmentioning
confidence: 99%